Multidisciplinary Approach to Cardiomyopathy in Pregnancy : From Diagnosis to Delivery Planning - Saleh, Obby; Lestari, Peby Maulina (Sriwijaya Journal of Medicine, 2025)
Cardiomyopathy in pregnancy, particularly peripartum cardiomyopathy (PPCM), is a rare but potentially life-threatening condition that poses serious risks to both maternal and fetal health. Its clinical manifestations, such as dyspnea, fatigue, and edema often resemble normal pregnancy symptoms, contributing to delayed diagnosis and treatment. This narrative review aims to summarize the etiology, diagnostic approach, and multidisciplinary management strategies for cardiomyopathy during pregnancy, focusing on PPCM, dilated cardiomyopathy (DCM), and other less common subtypes. Literature was obtained through a non-systematic search of PubMed, ScienceDirect, and Google Scholar for studies published between 2010 and 2025. Diagnosis is based on clinical evaluation, echocardiography, NT-proBNP, troponins, and exclusion of other causes. Management includes symptom control, prevention of arrhythmias and thromboembolism, and careful adaptation of standard heart failure therapy to the physiological changes of pregnancy. Medications such as beta-blockers, diuretics, and low molecular weight heparin are considered safe, while ACE inhibitors are contraindicated during gestation. The use of bromocriptine shows potential benefit in improving cardiac function but remains controversial due to the risk of thrombosis, requiring concurrent anticoagulation. Device therapy and mechanical support may be indicated in severe or refractory cases. Prognosis depends on cardiomyopathy subtype, timing of diagnosis, and left ventricular function recovery. Early recognition, close monitoring, and individualized care are essential to improve maternal and fetal outcomes. Further research is needed to guide safe and effective management strategies in pregnant patients with cardiomyopathy.